أثر النظام الجنائي الإسلامي في المبادئ الجنائية الوضعية - شيماء, الطيب; ابتهاج, داهش (جامعة الوادي university of eloued, 2023)
عنوان البحث: أثر مبادئ التشريع الجنائي الإسلامي على القوانين الوضعية "من الموضوعات المهمة التي تطرح إشكالية مدى تأثير القوانين الوضعية بمبادئ التشريع الجنائي الإسلامي؟ وللإجابة على هذه الإشكالية إعتمدنا المنهج المقارن والمنهج الإستقرائي والمنهج الوصفي والمنهج التحليلي وفق الخطة التالية: المبحث التمهيدي التعريف بممطلحات الدراسة والمبحث الأول ذكر أهم مبادئ التشريع الجنائي الإسلامي و المبحث الثاني تأثر مبادئ التشريع الجنائي الإسلامي على القوانين الوضعية،، وقد توصلنا إلى أهم النتائج والمقترحات: إن الفقه الإسلامي قد ترك في تشريعاتنا الجنائية، كما ترك في غيرها من التشريعات أثر كبيرا لا يمكن تجاهله بإعتباره مصدرا تاريخيا وفقهيا لكثير من المبادئ المعمول بها في النظم الجنائية، وخاصتا فيما يتعلق بالمسؤولية وما يتصل بها، وضرورة إنشاء مجلس إسلامي قانوني لضبط القوانين الوضعية أكثر. The Impact of the principles of islamic criminal legislation on man-made laws is one of the important topics that poses the problem of the extent of the influence of man-made laws on the principles of islamic criminal legislation? to answer this question , the study adopted the comparative, the inductive, the descriptive, and the analytical approach according to the following plan: the introductory chapter defines the terminology of the study and the chapter the first mentioned the most important principles of islamic criminal legislation, and the second chapter mentioned the influence of the principles of islamic criminal legislation on man-made laws. for many of the principles in force in criminal systems, especially with regard to responsibility and related matters, and the need to establish an islamic legal council to control man-made laws more.
مدكرة
Keywords: النظام الجنائي الإسلامي، المبادئ الجنائية الوضعية، التشريع الجنائي الإسلامي; The Islamic criminal system, positive criminal principles, Islamic criminal legislation